Multimodal retinal imaging of m.3243A>G associated retinopathy - Francesco Romano; Mariano Cozzi; Giovanni Staurenghi; Anna Paola Salvetti (American Journal of Ophthalmology Case Reports, 2022)
Retro-mode illumination imaging can provide good visualization of chorio-retinal atrophy and of the retinal pigment epithelial alterations occurring in m.3243A > G associated retinopathy.